Perceived Barriers and Challenges Among Migrant Nurses Working in the Middle East: A Scoping Review - WD, Fifi Dwi Andika; Agustina, Hana Rizmadewi; Yudianto, Kurniawan (GLOBAL HEALTH SCIENCE GROUP, 2024)
The Middle East is experiencing a significant shortage of nursing professionals, a situation exacerbated by various factors including rapid population growth, economic challenges, and healthcare demands. The movement of migrant nurses toward the Middle East has led many migrants to work as a nurse. While the influx of migrant nurses has had positive impacts on healthcare delivery, it has also introduced a range of challenges and barriers that affect both the nurses and the healthcare systems they support. Understanding these barriers and challenges among migrant nurses in the Middle East is essential to maintain retention that will lead to a decrease in the rate of migrant nurse turnover. There is a range of factors that contribute to barriers and challenges; however, summarizing these factors related to barriers and challenges among migrant nurses in the Middle East countries are none up to now. Purpose to identify, integrate, and summarize barriers and challenges among migrant nurses in the Middle East countries. Methods: This review applied the methodological framework for scoping reviews proposed by Arksey and O'Malley, and it is documented according to the PRISMA-ScR checklist. Searches were conducted across four electronic databases: Ebscohost, Science Direct, PubMed- and Google Scholar to locate primary research and gray literature published from 2005 to 2024. Titles and abstracts were screened based on inclusion and exclusion criteria, followed by a review of the full-text articles. The extracted data were summarized, and the findings were synthesized. There are several factors contributing for barriers and challenges experienced among migrant nurses working in middle east. These factors are categorized into three levels: the macro level, the meso level, and the micro level. By conducting research on the barriers and challenges faced by migrant nurses in the Middle East, stakeholders can work towards creating a more supportive, equitable, and sustainable healthcare environment that benefits both healthcare professionals and the communities they serve.